Health Communication Strategies to Reduce the Habit of Staying Up Late Among Students at Universitas Trunodjoyo Madura - Nihayatus Sakinah; Zahra Nabila (Literasi Nusantara, 2026)
The habit of staying up late (begadang) among university students has become a prevalent phenomenon with significant negative impacts on physical health, cognitive function, emotional stability, and academic performance. This study aims to analyze health communication strategies in reducing the habit of staying up late among students at Universitas Trunodjoyo Madura. Using a qualitative approach through a literature review combined with questionnaire data from 20 respondents across various faculties at UTM, the findings reveal that 65% of respondents frequently stay up late and 90% access social media at night before sleeping. The primary drivers include academic pressure, habitual gadget use, and social influence. Social media dominates as the main source of health information (80%). Effective health communication strategies identified include psychoeducation and sleep literacy, social media health campaigns, peer counseling, and institutional sleep hygiene policies. These integrated strategies are expected to raise students' awareness and promote healthier sleep habits among students at Universitas Trunodjoyo Madura.